The reconstruction of American liberalism, 1865-1914 - Cohen, Nancy L. (University of North Carolina Press, 2002)
Tracing the formation of liberal political ideology from the end of the Civil War to the early 20th century, Nancy Cohen offers an interpretation of the origins and character of modern American liberalism. She argues that these values and programmes were formulated in the Gilded Age.